Modeling cue-exposure therapy for alcohol use disorder in rhesus monkeys: Effects of putative cognitive enhancers. (1st February 2023) - Pareek, Tanya; Overton, John S.; Nguyen, Luat T.; Rahman, Md. Toufiqur; Sharmin, Dishary; Cook, James M.; Platt, Donna M.
Abstract: Background: Cue-exposure therapy (CET) is an effective approach for anxiety-related disorders, but its effectiveness for substance use disorders is less clear. One potential means of improving CET outcomes is to include a cognitive-enhancing pharmacotherapy. This study evaluated d -cycloserine (DCS) and RY-023, putative cognitive enhancers targeting glutamate and GABA systems, respectively, in a monkey model of CET for alcohol use disorder. Methods: Male rhesus monkeys (n = 4) underwent multiple cycles of the CET procedure. During baseline (Phase 1), monkeys self-administered an ethanol solution under a fixed-ratio schedule and limited access conditions such that every 5th response in a 3-h session resulted in 30-s access to a drinking spout and a change in ethanol-paired cue lights from white to red. Behavior then was extinguished (Phase 2) by omitting the ethanol solution yet retaining the ethanol-paired stimulus lights. Monkeys also received injections of vehicle, DCS (3 mg/kg), a partial agonist at the glycine modulatory site on glutamatergic NMDA receptors, or the α5GABAA receptor-selective inverse agonist RY-023 (0.03 or 0.3 mg/kg). Once responding declined, monkeys underwent a cue reactivity test (Phase 3), and then returned to self-administration the following day to assess reacquisition (Phase 4). Results: Through multiple cycles, self-administration remained stable. Compared to vehicle, DCS facilitated extinction of ethanol seeking (Phase 2) and delayed reacquisition of ethanol self-administration (Phase 4). In contrast, RY-023 facilitated extinction (Phase 2) and reduced cue reactivity (Phase 3). Conclusions: Adjunctive pharmacotherapy can improve CET outcomes, but the choice of pharmacotherapy should be dependent on the outcome of interest. Highlights: Adjunctive pharmacotherapies may improve outcomes of cue-exposure therapy (CET). D -cycloserine facilitated extinction and slowed resumption of self-administration. RY-023 facilitated extinction and attenuated cue reactivity. Glutamatergic and GABAergic compounds differentially enhance specific CET outcomes.